The Sediment Selectivity of Perinereis aibuhitensis Larvae: Active or Passive? - Fang, Jinghui; He, Wei; Meng, Shan; Jiang, Zengjie; Fang, Jianguang; Mao, Yuze; Liang, Bo (Frontiers in Marine Science, 2021)
The selectivity of larvae Perinereis aibuhitensis on different sediment types was studied using an experimental behavioral device in the lab. There were six types of sediment with different organic matter content: 2.19%, 2.30%, 2.86%, 3.25%, 3.51%, and 5.52%. The results indicated significant differences in the six treatments' organic matter content (p < 0.05). When the larvae P. aibuhitensis initially attached to the sediment, the larvae's density showed no significant difference among the six treatments. The density of larvae decreased gradually during the experimental period. It increased with the increasing organic matter content in sediment at every sampling time, but there was no significant difference (p > 0.05). The larvae's specific growth rate in the first month was significantly higher than those in the second and third months (p < 0.05). The mortality showed no significance at different sediments in equal sampling times, but the mortality was lower in high organic matter content sediments. This study showed that the larvae P. aibuhitensis did not make an active selection; random selection happened when initially attached to the sediment with different organic matter contents. Higher organic matter content in the sediment was more conducive to larvae survival, and the organic matter content is the limitation on the mortality and the density. The different densities in the natural habitat of P. aibuhitensis might occur due to the passive selection by the environment.